Caracterização e desenvolvimento de processos térmicos para a aplicação do rejeito jarosita - Vinícius Fernando Coelho Sampaio (2022)
Mining activity is responsible for numerous environmental impacts, such as tailings dams. Zinc is a metal of appreciable economic value and its production occurs predominantly by hydrometallurgical processes. The RLE hydrometallurgical route is used by the mining company involved in this research and produces huge amounts of jarosite tailings monthly. The objective of this work was to carefully study jarosite and propose two thermal treatment routes in an oxidizing and reducing atmosphere, in order to recover the gases of interest NH3 and SO3 and seek viable applications for the solid formed at the end of heating. Furthermore, the possibility of forming an acid solution from the dissolution of SO3 in H2O was studied. Initially, jarosite was characterized by different physicochemical techniques, namely: Thermogravimetric Analysis (TG), X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Energy Dispersion X-Ray Spectroscopy (EDS) Microanalysis, X-Ray Fluorescence (FRX), Elemental Analysis by CHN, Elemental Analysis by Atomic Absorption and Elemental Analysis by ICP-OES. These characterizations were fundamental to identify the temperatures where the emission of gases occurs, the structural, morphological and chemical characteristics of jarosite. Two heat treatment atmospheres were proposed: oxidizing and reducing. In the oxidizing atmosphere, an Ar flow was used and in the reducing one, H2/N2 or CO, from the burning of charcoal. The gas recovery rates and the concentration of the solution formed by the dissolution of SO3 in H2O were quantified by acid-base titrations. The solid samples obtained in the two heat treatment atmospheres, as well as the jarosite, were characterized by different physicochemical techniques, in order to identify the crystalline transformations that occurred during heating, the mineralogical composition and the quantification of the main mineral phases present in the end of reactions. It was proposed to scale the amount of jarosite subjected to heat treatment using a steel reactor without controlled gas flow and an industrial rotary kiln. The solid materials obtained in these new systems were also characterized. Finally, a technical and economic feasibility study was carried out to assess whether the thermal routes proposed in this work are capable of generating economic value for the mining company and minimizing the environmental impacts caused by its extractive activity.